Penerapan Gaya Kepemimpinan Transformasional Dalam Manajemen PAUD di Kecamatan Sidorejo Salatiga - Mei Hardika Senny; Lanny Wijayaningsih; Mozes Kurniawan (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
The purpose of this study is to prove that the transformational leadership style can be applied and to describe how it is applied in Early Childhood Education management in Sidorejo District of Salatiga. This descriptive qualitative research used the sampling using technique purposive. Techniques of collecting data using interviews, observation and documentation. Many phenomena researchers find in some kindergartens in the city of Salatiga are examples: many teachers resigned each year, they lack of motivation and awareness of their duties as teachers or perform tasks only because of rewards or punishment, and lack of trust and loyalty to the institution school. With the implementation of this transformational leadership style, it provides some positive impacts, principals being role models, encouraging subordinate performance, harmonizing the work environment, empowering employees, acting on the value system, continuously improving their capabilities, and having the ability to cope with complex situations. So with this study, the authors hope this transformational leadership style can be applied in school institutions that have not used this style of leadership, especially early childhood institutions because the results show that the transformational leadership style is very effective applied to early childhood education management.